The developmental dynamics between causal attributions and self-concept of ability from 7th grade through 9th grade - Palosaari, Anna-Leena (2014)
The aim of the present study was to investigate how and to what extent mathematics- and Finnish language-related causal attributions and self-concept of abilities related among adolescents in upper comprehensive school. The present study also examined whether it is self-concepts that predict subsequent attributions or vice versa. A total of 237 students participated in the study. The data was gathered via questionnaires (attributions and self-concepts) and tests (performance in math and in Finnish language) when the students were in 7th grade and again when they were in 9th grade. The results showed that in both school subjects high self-concept was associated with internalizing success and externalizing failure. The only exception was that in 9th grade mathematics adolescents with high self-concept were more likely to attribute failure to effort than to lack of guidance, thus indicating some sense of control over failure outcomes. Overall, the results suggest that adolescents with high self-concept show signs of an adaptive attributional style and adolescents with low self-concept show signs of a maladaptive attributional style. The results showed further that it was previous self-concept that predicted subsequent attributions rather than vice versa: self-concepts were positively related to attributing subsequent success to abilities, and attributing failure to lack of guidance, and negatively related to attributing subsequent success to task and attributing failure to ability in both school subjects. Only one attribution was related to subsequent self-concept among boys: the more boys attributed their failure in mathematics to lack of guidance, the better their subsequent self-concepts in 9th grade were. Also, particularly girls with higher self-concept of math were less likely to attribute their subsequent success to easiness of the task. On the basis of the results it can be concluded that good academic self-concept supports the development of adaptive attributional style whereas low self-concept might put adolescents at risk of maladaptive attributional style. Furthermore, the results cautiously suggest that the effect of causal attributions on subsequent self-concept of ability and the effect of self-concept on subsequent attributions might be different for boys and girls, and that these differences might also depend on the school subject in question. Overall, the results reinforce the importance of supporting adolescents' self-concepts.